Uncertainty of Governmental Relief and the Crowding out of Insurance - Paul A. Raschky; Reimund Schwarze; Manijeh Schwindt; Ferdinand Zahn (University of Innsbruck, Department of Public Finance, 2010)
This paper discusses the problem of crowding out of insurance by co-existing governmental relief programs - so-called 'charity hazard' - in a context of different institutional schemes of governmental relief in Austria and Germany. We test empirically whether an assured partial relief scheme (as in Austria) drives a stronger crowding out of private insurance than a scheme promising full relief which is subject to ad hoc political decision making (as in Germany). Our general finding is that the institutional design of governmental relief programs significantly affects the demand for private natural hazard insurance.
Keywords: D78; D81; G22; Q54; 330; Insurance demand; governmental relief; natural hazards; Naturkatastrophe; Katastrophenhilfe; Elementarschadenversicherung; Nachfrage; Deutschland; Österreich